Guided imagery targeting exercise, food cravings, and stress: a multi-modal randomized feasibility trial - Giacobbi, Peter (J Behav Med, 2017)
The purpose of this randomized wait-list controlled trial was to test the feasibility and preliminary efficacy of a guided imagery based multi-behavior intervention intended to address psychological stress, food cravings, and physical activity. Personalized guided imagery scripts were created and participants were instructed to practice guided imagery every day for 35 consecutive days. Of 48 women who enrolled, we report comparisons between 16 randomized to treatment with 19 who were wait-listed (overall M(age) = 45.50; M(bodymassindex) = 31.43). Study completers reported 89% compliance with practicing guided imagery during the intervention. A significant time-by-group interaction was observed with reductions in food cravings and increases in physical activity compared with wait-list controls. Telephone-based multi-behavior interventions that utilize guided imagery to address food cravings and exercise behavior appear to be acceptable for overweight and obese women. Future phone-based guided imagery research testing this skill to address multiple health behaviors is justified.